Design of a Palm Oil Harvest Recording Information System using Two-Factor Authentication Security - Jefry Subastian; Mansur Mansur (Universitas Islam Indragiri, 2026)
The palm oil harvest recording process in many farmer groups is still carried out manually, which may lead to recording errors, delays in reporting, and difficulties in verifying harvest data. This study aims to design and develop a web-based palm oil harvest recording information system that supports harvest data entry by farmers, harvest verification by agents, transportation monitoring by drivers, and the presentation of harvest information through a dashboard for the owner. The system is designed by integrating a Two-Factor Authentication (2FA) security mechanism using One-Time Password (OTP) verification as an additional authentication layer to enhance user access security. The software development method applied in this study is the System Development Life Cycle (SDLC) Waterfall model, which includes requirement analysis, system design, implementation, testing, and maintenance stages. Black-box testing results indicate that all main system features function properly according to user requirements. In addition, user acceptance testing using usability testing with the System Usability Scale (SUS) instrument obtained an average score of 72.5, which falls into the Good category. These results suggest that implementing OTP-based 2FA improves authentication security without reducing system usability. The developed system is able to enhance the efficiency, accuracy, and transparency of the palm oil harvest recording process and has the potential to be implemented in farmer groups or similar business units.